Improvement of collapsing problematic soils on the sabzevar-mashhad railway route (northeast of Iran) using traditional additives - Hashemi, Hamid; Yazdi, Abdollah; Teshnizi, Ebrahim Sharifi (Nexo Revista Científica, 2023)
Collapsing soils are among the problematic soils in geotechnical engineering. These soils have a relatively good resistance in their natural state with low humidity, but in case of saturation without change in the incoming load or subjected to vibration force, they settle a lot and in many cases, it will cause cracking or destruction of foundations, roads, railway lines, dams, pipelines and other existing structures. Collapsing soils are scattered in many regions of the world, in Iran these soils are mostly observed in the central and eastern regions. In this research, according to the samples taken from Khorasan-Razavi province in the area of Sabzevar-Mashhad, these samples have been shown to be in the category of collapsing soils based on the tests performed according to ASTM standards. In order to improve this soil, cement and lime additives with percentages of 5 and 10 percent have been used, which has improved the shear properties of the soil due to the addition of lime and cement, so that it causes an increase in the friction angle in the soil, which indicates an improvement in the soil parameters. The results obtained with regard to the addition of cement and lime to the compacted soil show that the index of compaction in the addition of lime is better than that of cement and the results show that with the increase of lime, the soil has a 68% and 78% decrease in the soil compaction index, respectively, but when cement is added to the soil, it causes the percentage of raking index to improve by 34 and 37%.